(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this article we introduce ts-neighbourhoods using Sin-open sets in trigonometric topological spaces. In addition, we examine their basic properties. Furthermore, we introduce and study the fundamental properties of ts*-Neighbourhoods in trigonometric topological spaces.